Efficacy of Harpin protein in stimulating wheat resistance against bacterial leaf streak Xanthomonas translucens (Damascus University Journal of agriculture sciences, 2025)
In this article، the activity of  Harpin protein in reducing the pathogenicity of the Bacterium Xanthomonas translucens  which caused Bcterial leaf streak (BLS) on wheat was evaluated. Two isolates of the pathogen Xt10 and Xt4.2were used، and the wheat cultivar Sham 6 which is susceptible to disease. Harpin treatment showed decreasing in infection severity in both isolates (14.8، 13.2)%. respectively compared to the control ; Whereas، the rate of infection severity with isolate Xt10 was 6.4% in wheat seedlings treated with Harpin compared to control which was 43.2%، while in seedlings infected with the isolate Xt4.2 it reached (5.2، 39.2)% for seedlings treated with Harpin and water، respectively، decrease infection severity of the two isolates was associated with a decrease in bacterial growth in the tissues. Where the decrease in the bacterial count of the two isolates began 72 hours after infection، and the count was 50  times less in the plants treated with Harpin compared to control for  isolate Xt10 and 120 times lower for Xt4.2 isolate. As a result، harbin protein is effective in reducing the pathogenicity of BLS on wheat plant.
Keywords: Harpin; Wheat; Resistance; Bacterial leaf streak.